Morfofisiologia e bioquímica de plantas de cedro e ipê-roxo expostas ao cobre em sistema hidropônico - Kuinchtner, Caroline Castro (2021)
Cedrela fissilis Vell. (Cedar) and Handroanthus heptaphyllus (Vell.) Mattos (Ipê-roxo) are native Brazilian forest species that have great forestry and ecological relevance. Thus, to know the forestry of these species, the edaphic knowledge in which they are found is of great importance, as well as the species responses to the variations that occur in different places. In this sense, in recent years, Brazilian soils have suffered great disturbances, mainly with copper (Cu) contamination, causing problems for plant development and growth. Thus, the research aimed to characterize morphophysiological, biochemical and tissue analysis variables in cedar and Ipê-roxo seedlings exposed to Cu in a hydroponic system, in a greenhouse, in addition to verifying the tolerance of species to Cu. After emergence and initial growth of the seedlings (about 10 cm in height), they were removed from the substrate and transferred to the hydroponic system. After a week of acclimatization, these seedlings were subjected to different concentrations of Cu: 0 (complete nutrient solution), 2, 4, 6 and 8 mg L-1, with four replicates per treatment and 16 plants per repetition. After 21 days of exposure to the treatments, morphophysiological attributes were analyzed, such as increase in number of leaves, height and length of roots, dry biomass, leaf area, and photosynthetic variables. In addition, biochemical variables were also evaluated: photosynthetic pigments, antioxidant enzymes, lipid peroxidation, hydrogen peroxide content and tissue Cu analysis. For cedar seedlings, it was observed that Cu concentrations negatively affected the increase in shoot, roots, number of leaves, net assimilation rate, stomatal conductance, transpiration rate and rubisco carboxylation efficiency, compared to the control treatment. In general, Cu promoted an increase in the activity of the antioxidant enzymes superoxide dismutase and guaiacol peroxidase. The lipid peroxidation in the roots increased with the highest Cu indices. Furthermore, a higher Cu content was observed only in the roots of C. fissilis seedlings with the increase in the Cu concentration in the growth medium. For the variables increase in shoot, shoot dry mass, root dry mass and photosynthetic pigments of H. heptaphyllus, there was no difference independent of the tested Cu concentrations. Furthermore, the net assimilation rate and transpiration rate were negatively affected only in the highest Cu concentration (8 mg L-1), and this promoted an increase in the activity of antioxidant enzymes, mainly in the root system. On the other hand, it was observed that the application of Cu generated higher content of H2O2 and lipid peroxidation in the roots. Therefore, the presence of Cu in the nutrient solution negatively altered the biochemical and physiological variables of C. fissilis seedlings, being harmful to their growth, and thus, a sensitive behavior of the species was observed. On the other hand, H. heptaphyllus in general was affected by Cu only with 8 mg L-1, being accumulated mainly in the roots, without registering a decrease in root and shoot biomass, which may indicate tolerance of the species to this metal. Due to these characteristics, C. fissilis plants can be used as markers of areas contaminated with Cu, while H. heptaphyllus seedlings have potential for use in phytoremediation of soils contaminated by Cu.